Efeito acaricida de produtos naturais e sintéticos de plantas e solventes sobre Boophilus Microplus (canestrini, 1887) (acari: Ixodidae) - Ana Carolina de Souza (2001)
This study was conducted at the Laboratory of Acarology Embrapa Gado de Leite Juiz de Fora, Minas Gerais, where three different experiments were done with the tick Boophilus microplicae. 1) The first experiment studied the larvicidal activity of 33 derivatives of arilsulfonilicos (+) - camphor and (+) - isopinocanfona. 2) In the second experiment study evaluated the effect of acaricide essential oils and concentrated emulsion of the genus Ecalyptus on larvae and engorged. The citroclal is the main component of oil of E. citriodora, being responsible for his action acaricide. 3) The third experiment tested the sensitivity of larvae and engorged females of different solvents in three methods. The use of oil in test larvae impregnated paper was not necessary, but not in the immersion test of female maturation engorged with hydrophilic compounds. The average mortality caused by solvents was less in the tests with impregnated paper, increased in the immersion test larvae and females. Solvents with low molecular weight and viscosity did not affect the average mortality, especially at concentrations below 76%. The use of the control group in these tests is essential